2012
DOI: 10.1080/00036846.2011.587778
|View full text |Cite
|
Sign up to set email alerts
|

Testing equity market efficiency around terrorist attacks

Abstract: This article uses the nine major bombings since 1998 that have been attributed to Al Qaida to examine market efficiency, including a test of rumours that investors traded with advance knowledge of attacks. Analysis of these related, but individually unexpected, events confirms markets are semi-strong efficient: it now takes well under a trading day to fully price in a completely unexpected attack. On balance, markets also proved strongly efficient with no conclusive evidence of insider trading.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Indeed, in the words of Johnston and Nedelescu (2006, p. 9) when discussing the terrorist attacks of September 11th, financial markets are well built for ‘digesting the information on the economic and financial impact of the terrorist attacks after an initial shock and efficiently incorporating the information into asset prices so that it could be integrated into decisions about the future’. Coleman (2012) proves this point in an examination of high-profile terrorist attacks, concluding that modern capital markets are semi-strong efficient in absorbing the information from terrorism (that is, market prices reflect all past fundamental information about stocks as well as all public information currently available, including the possible effect of terrorism). In the face of an unexpected bout of political violence, capital markets should still be able to analyze the possible ramifications and adjust to the information which has been provided.…”
Section: IImentioning
confidence: 97%
“…Indeed, in the words of Johnston and Nedelescu (2006, p. 9) when discussing the terrorist attacks of September 11th, financial markets are well built for ‘digesting the information on the economic and financial impact of the terrorist attacks after an initial shock and efficiently incorporating the information into asset prices so that it could be integrated into decisions about the future’. Coleman (2012) proves this point in an examination of high-profile terrorist attacks, concluding that modern capital markets are semi-strong efficient in absorbing the information from terrorism (that is, market prices reflect all past fundamental information about stocks as well as all public information currently available, including the possible effect of terrorism). In the face of an unexpected bout of political violence, capital markets should still be able to analyze the possible ramifications and adjust to the information which has been provided.…”
Section: IImentioning
confidence: 97%
“…When directly analysing semi-strong form market efficiency, most researchers chose typical events such as splitting/merging the stocks or announcements of dividend payments. Some authors also analysed stock price developments after atypical, but significant events such as terrorist attacks (Coleman, 2012). Sturm (2013) investigated stock market reaction to announcements of operational losses in European financial companies and found significant negative stock price reaction to first press announcement of operational losses.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Since the 1970s, most of the studies had been carried out in the largest, most developed stock markets: USA (Chance, 1985) Australia (Goss, 1983), Greece (Alexakis, Patra and Poshakwale, 2010;Apergis and Eleptheriou, 2001;Siourounis, 2002), Hong Kong, United Kingdom, Japan (Coleman, 2012) and others. Even though this topic has not been widely investigated in the Baltic stock markets, Gausiene and Jureviciene (2010), Klimasauskiene and Moscinskiene (1998), Konceviciene (2006), Leipus and Norvaisa (2003) carried out studies in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found that increased market resilience can be created if the financial sector endows appropriate liquidity to promote market stability and suppress panic. Another study carried out by Coleman (2012) examined the effectiveness of the capital market following the terrorist attacks by the Al-Qaeda organization. The study examined the effect of the incident on indices and the commercial profitability of investors with inside information like the Al-Qaeda organization.…”
Section: Jfc 232mentioning
confidence: 99%
“…One study that examined these effects was conducted by Suleman (2012) Coleman (2012) examined the effectiveness of the capital market following the terrorist attacks of the Al-Qaeda organization. The study examined the effect of the incident on indices and on commercial profitability of investors with inside information like the Al-Qaeda organization.…”
Section: Introductionmentioning
confidence: 99%